Survival after T cell–depleted haploidentical stem cell transplantation is improved using the mother as donor - Stern, Martin (American Society of Hematology, 2008)
We hypothesized that transplacental leukocyte trafficking during pregnancy, which induces long-term, stable, reciprocal microchimerism in mother and child, might influence outcome of patients with acute leukemia given parental donor haploidentical hematopoietic stem cell transplantation (HSCT). We analyzed the outcome of 118 patients who received transplants for acute leukemia in 2 centers. Patients received highly T cell–depleted haploidentical grafts after myelo-ablative conditioning. Five-year event-free survival was better in patients who received transplants from the mother than from the father (50.6% ± 7.6% vs 11.1% ± 4.2%; P < .001). Better survival was the result of both reduced incidence of relapse and transplantation-related mortality. The protective effect was seen in both female and male recipients, in both lymphoid and myeloid diseases; it was more evident in patients receiving transplants in remission than in chemotherapy-resistant relapse. Incidences of rejection and acute graft-versus-host disease were not significantly influenced. Multivariate analysis confirmed donor sex in parental donor transplantation as an independent prognostic factor for survival (hazard ratio, father vs mother = 2.36; P = .003). In contrast, in a control cohort of patients who received transplants from haploidentical siblings, donor sex had no influence on outcome. Although obtained in a retrospective analysis, these data suggest that the mother of the patient should be preferred as donor for haploidentical HSCT.